IEEE International Geoscience and Remote Sensing Symposium
DOI: 10.1109/igarss.2002.1027252
|View full text |Cite
|
Sign up to set email alerts
|

Phase functions of light scattering measured in waters of world ocean and lake Baykal

Abstract: -A set of twenty previously unpublished phase functions of light scattering measured in situ in waters of oceans, seas and lake Baykal is presented in the tabular form. In 18 cases these measurements were accompanied by the independent measurements of beam attenuation coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
3
9
0
Order By: Relevance
“…Recently, based on VSFs observations in the southern Baltic Sea, Freda (2012) [12] found that φp(140,λ) increases linearly with wavelength (r 2 >0.99). Using our measured VSFs as well as tabulated VSFs in the literature [17][18][19][20][21], we verify this relation; we compare bbp, Freda, bbp(λ) estimated using φp(140,λ) derived from this relation in Eq. (4), with bbp, integral, bbp(λ) directly determined using Eq.…”
Section: B Particulate Conversion Factor For B Bp (λ)supporting
confidence: 59%
See 1 more Smart Citation
“…Recently, based on VSFs observations in the southern Baltic Sea, Freda (2012) [12] found that φp(140,λ) increases linearly with wavelength (r 2 >0.99). Using our measured VSFs as well as tabulated VSFs in the literature [17][18][19][20][21], we verify this relation; we compare bbp, Freda, bbp(λ) estimated using φp(140,λ) derived from this relation in Eq. (4), with bbp, integral, bbp(λ) directly determined using Eq.…”
Section: B Particulate Conversion Factor For B Bp (λ)supporting
confidence: 59%
“…Quantified errors from the fixed-angle approach using νp [Rp(120,170)] and χp, mean(120) are provided in the third and fourth columns of Table 4. We evaluated 411 VSF datasets, including VSFs measured here (N=304) and VSFs from the literature (N=107) [17][18][19][20][21].…”
Section: Table 4 Summary Of Quantified Errors In the Fixed-angle Appmentioning
confidence: 99%
“…1). For example, B p values estimated from our measured VSFs vary over a factor of 30 from 0.0015 to 0.0543, which is much greater than the range of 0.0073-0.0194 estimated from Petzold's measurements and the range of 0.002-0.020 measured in Tonizzo et al [16], but comparable to the range of 0.0015-0.0454 reported in Mankovsky and Haltrin [34,35] over the oceans and lakes worldwide.…”
Section: Introductionsupporting
confidence: 54%
“…For example, the averaged ratio of R − R 0 to R exceeds 0.05 (5%) when c · h ¼ 10 −0.2 ≅ 0.63 and r b ¼ 0.4, as indicated in the figure by the symbol "×." Here, a c · h value of 0.63 corresponds to an h value of 2.1 m when c ¼ 0.3, and both of these values are not too small to be common: c < 0.3 has been observed in various locations in oceans and the Mediterranean for green wavelengths 19,23 and in a coral reef even at 660 nm. 29 An r b value of 0.4 is not a large value for carbonate sand in coral reefs: the average r b of 670 measurements by Hochberg 24 falls within 0.4 to 0.6 at wavelengths of 475 to 700 nm.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…The c · h range handled in this paper corresponds to 0.05 to 19.91 m when c ¼ 0.2 (a possible value for clear seawater at blue and green wavelengths). 18,19,23 We set r b to cover a wide range of 0.1 to 0.6 with a small interval of 0.05. An r b value of 0.6 is possible for carbonate sand at green and red wavelengths.…”
Section: Radiative Transfer Simulationmentioning
confidence: 99%